Synthesis of nanocrystalline rutile - Samuel, V; Pasricha, R; Ravi, V (Ceramics International, 2005)
Nanocrystalline titanium dioxide (TiO2) in the rutile phase has been obtained by homogeneous precipitation using urea and TiOCl2. A mixture of urea and TiOCl2 is heated on a hot water bath at 65-75 degrees C to precipitate rutile powders. X-ray diffraction (XRD) studies on these oven-dried powders indicated the formation of single-phase rutile. Raman scattering experiments were also performed to confirm the formation of the rutile phase. Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 40 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; Electron microscopy; powders; TiO2; X-ray methods

TiO2 ceramic varistor modified with tantalum and barium - Gaikwad, A. B.; Navale, SC; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
The non-linear current (I)-voltage (V) characteristics of titanium dioxide doped with small quantities of tantalum and barium (99.9 TiO2 + 0.1 Ta and 99.4 TiO2 + 0.1 Ta + 0.5 Ba, all are in at.%) were investigated. These samples have the non-linear coefficient (alpha) values of (20-30) with high breakdown voltages (E-B similar to 400-700 V mm(-1)). The pentavalent tantalum acts as donor and increases the electronic conductivity. The higher electrical conductivity and decrease in the breakdown field strength with barium addition is attributed to higher density. The acceptor like surface states formed by barium ions segregate to grain boundaries due size misfit to thereby modifying the electrical barrier characteristics of grain boundaries. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Oxides; TiO2; varistor; X-ray diffraction

Varistors based on Ta-doped TiO2 - Navale, S. C.; Murugan, A. Vadivel; Ravi, V. (Ceramics International, 2007)
The nonlinear current (I)-voltage (V) characteristics of titanium dioxide are examined when doped with small quantities (0.05-0.5 at.%) of tantalum pentaoxide. For optimum compositions, the nonlinear coefficients are found to be in the range of 25-30 and the breakdown field strength (EB) is similar to 4000 V/cm. The obtained alpha- and E-B-values are higher than the previously reported values for TiO2 ceramics. The acceptor like surface states at the grain boundary adsorb oxygen during sintering and cooling, leading to formation of grain boundary barrier. The grain boundary barrier height (OB) is calculated using Schottky equation. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Oxides; Schottky barrier; TiO2; varistor

N,S-Co-doped TiO2 Nanophotocatalyst: synthesis, electronic structure and photocatalysis - Sathish, M.; Viswanath, R. P.; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2009)
N,S-co-doped anatase-phase TiO2 (N,S-TiO2) nanophotocatalysts were prepared from either benzothiazoline or aminothiol with titanium isopropoxide followed by a systematic thermal decomposition. The chemical nature of S and N in N,S-TiO2 have been identified by XPS to be sulfate and NO-like, respectively. A significant band broadening and red-shift in the UV-visible absorption spectrum of N,S-TiO2 suggests a band gap reduction compared to TiO2. A maximum band-gap narrowing of 0.22 +/- 0.02 eV was observed on N,S-TiO2. Higher energy width observed on N,S-TiO2 is in contrast to 0.13 eV from N-doped TiO2 indicating the sulfate-like species might play a major role in narrowing the band-gap to a Higher level. It is confirmed that the oxidation of N and S to NO and SO42- occurs in the final stage of preparation of N,S-TiO2, during calcination in air. It is predicted that the oxygen associated with sulfate and NO structural features could be crucial in bringing down the energy gap and red shift in optical absorption and the role of sulfur is to facilitate the above. Photocatalytic decomposition of methylene blue has been carried out on N,S-TiO2 shows higher activity than the commercial TiO2 in the visible region. However, sulfate species seems to enhance the activity of N,S-TiO2 marginally compared to N-TiO2, and possible suggestions are given to improve the same.
Keywords: nitrogen; Photocatalyst; Sulfur; TiO2; Visible Light Absorption

Support modification to improve the sulphur tolerance of Ag/Al2O3 for SCR of NOx with propene under lean-burn conditions - Jagtap, Neelam; Shubhangi B. Umbarkar; Miquel, Pierre; Granger, Pascal; Dongare, Mohan K. (Applied Catalysis B-Environmental, 2009)
Ag/Al2O3 catalysts with 1 wt% SiO2 or TiO2 doping in alumina support have been prepared by wet impregnation method and tested for sulphur tolerance during the selective catalytic reduction (SCR) of NOx using propene under lean conditions, Ag/Al2O3 showed 44% NOx conversion at 623 K, which was drastically reduced to 21% when exposed to 20 ppm SO2. When Al2O3 support in Ag/Al2O3 Was doped with 1 wt% SiO2 or TiO2 the NOx conversion remained constant in presence of SO2 showing the improved sulphur tolerance of these catalysts. Subsequent water addition does not induce significant deactivation. On the contrary, a slight promotional effect on the activity of NO conversion to nitrogen is observed after Si and Ti incorporation. FTIR study showed the sulphation of silver and aluminum sites of Ag/Al2O3 catalysts resulting in the decrease in the formation of reactive intermediate species such as -NCO, which in turn decreases NOx conversion to N-2. In the case of Ag/Al2O3 doped with SiO2 or TiO2, formation of silver sulphate and aluminum sulphate was drastically reduced, which was evident in FTIR resulting in remarkable improvement in the sulphur tolerance of Ag/Al2O3 catalyst. These catalysts before and after the reaction have been characterized with various techniques (XRD, BET surface area, transmittance FTIR and pyridine adsorption) for physico-chemical properties. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag/Al2O3; Aluminum sulphate; DRIFTS; Selective catalytic reduction; Silver sulphate; SiO2; Sulphur tolerance; TiO2

Effect of leakage current and dielectric constant on single and double layer oxides in MOS structure - Laha, Pinaki; Panda, A. B.; Dahiwale, S.; Date, Kalyani S.; Patil, K. R.; Barhai, P. K.; Das, A. K.; Banerjee, Indrani; Mahapatra, S. K. (Thin Solid Films, 2010)
MOS structure of Al/Al2O3/n-Si, Al/TiO2/n-Si and Al/Al2O3/TiO2/n-Si was obtained by deposition of Al2O3 and TiO2 on silicon substrate by RF Magnetron Sputtering system. The total thickness of the oxide layer similar to 40 +/- 5 nm in the MOS structure was kept constant. Samples were characterized by X-Ray diffraction (XRD). X-Ray photoelectron spectroscopy (XPS), Impedance analyzer and Current-voltage (J-V) characteristics. The variations in the dielectric constant and tan 8 of the MOS capacitor in the frequency range of 1000Hz-1MHz were measured by impedance analyzer. The variation in dielectric constant of the Al/Al2O3/TiO2/n-Si multilayer compared to single layer of Al/Al2O3/n-Si and Al/TiO2/n-Si is due to high probability of defects, lattice mismatch and interface interactions. The steep rise of Tan 6 values in the Al/Al2O3/TiO2/n-Si structure is due to the resonance effect of both Al2O3 and TiO2 layers. The leakage current mechanisms of MOS structures were extracted from Schottky coefficient and Poole-Frenkel coefficient. Theoretical values of Schottky coefficients (beta(SC)) and Poole-Frenkel coefficients (beta(PF)) for each sample were estimated using the real part of the dielectric constant. The experimental values were calculated from J-V characteristics and compared with theoretical values. The appropriate model has been proposed. It was found that Schottky and Poole-Frenkel mechanisms are applicable at low and high field respectively for all MOS structures. The combination of Al/Al2O3/TiO2/n-Si is found to be a promising structure with high dielectric constant and low leakage current suitable for MOS devices. (C) 2010 Elsevier B.V. All rights reserved.
37th International Conference on Metallurgical Coatings and Thin Films, San Diego, CA, APR 26-30, 2010
Keywords: Al2O3; dielectric constant; Leakage current; MOS device; Poole-Frenkel emission; Schottky emission; TiO2

Photocatalytic degradation of Azo dyes using Au:TiO2, gamma-Fe2O3:TiO2 functional nanosystems - Jagadale, Tushar C.; Kulkarni, Manjusha; Pravarthana, D.; Ramadan, Wegdan; Thakur, Pragati (Journal of Nanoscience and Nanotechnology, 2012)
We report photocatalytic degradation studies on Navy Blue HE2R (NB) dye on significant details as a representative from the class of azo dyes using functional nanosystems specifically designed to allow a strong photocatalytic activity. A modified sol-gel route was employed to synthesize Au and gamma-Fe2O3 modified TiO2 nanoparticles (NPs) at low temperature. The attachment strategy is better because it allows clear surface of TiO2 to remain open for photo-catalysis. X-ray diffraction, Raman and UV-VIS spectroscopy studies showed the presence of gold and iron oxide phases along-with the anatase TiO2 phase. TEM studies showed TiO2 nanocomposite particles of size similar to 10-12 nm. A detailed investigation on heterogeneous photocatalytic performance for Navy Blue HE2R dye was done using the as-synthesized catalysts Au:TiO2 and gamma-Fe2O3:TiO2 in aqueous suspension under 8 W low-pressure mercury vapour lamp irradiation. Also, the photocatalytic degradation of Amranth and Orange G azo dyes were studied. The surface modified TiO2 NPs showed significantly improved photocatalytic activity as compared to pure TiO2. Exposure of the dye to the UV light in the presence of pure and gold NPs attached TiO2 catalysts caused dye degradation of about similar to 20% and similar to 80%, respectively, in the first couple of hours. In the presence of gamma-Fe2O3 NPs attached TiO2, a remarkable similar to 95% degradation of the azo dye was observed only in the first 15 min of UV exposure. The process parameters for the optimum catalytic activity are established which lead to a complete decoloration and substantial dye degradation, supported by the values of the Chemical Oxygen Demand (COD) similar to 93% and Total Organic Carbon (TOC) similar to 65% of the treated dye solution after 5 hours on the employment of the UV/Au:TiO2/H2O2 photocatalytic process.
Keywords: Azo Dye; COD; H2O2; Photocatalysis; TiO2

Phase, size and shape transformation by fungal biotransformation of bulk TiO2 - Khan, Shadab Ali; Ahmad, Absar (Chemical Engineering Journal, 2013)
Nanosynthesis is an ever expanding frontier in recent years in view of its implications to many future technologies covering diverse fields. Considerable progress has been made realizing high quality synthesis of elemental nanomaterials as well as compounds as chemical, biological and physical routes. The issue of technologically viable large scale synthesis still continues to be a challenge. Here we demonstrate a novel environmentally friendly top down approach to nanosynthesis which exploits the strength and peculiarities of fungus based bioleaching in extracting radicals from compounds and then providing them with a reactive as well as capping environment. Thus protein capped nanoparticles of TiO2 (5-28 nm, circular and brookite phase) are formed directly from micron size (150-250 nm, disc shape, anatase phase) powder by exposing them to a medium of fungus Humicola sp. at just 50 degrees C. The fungus Humicola sp. is not only useful for the synthesis of nanoparticles but also for the transformation of shape, phase and size of TiO2. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Anatase; Biotransformation; Brookite; humicola sp; TiO2

Synthetic precursor to vertical TiO2 nanowires - Mishra, Biswajit; Ghildiyal, P.; Agarkar, Shruti A.; Khushalani, Deepa (Materials Research Express, 2014)
An easy protocol for improvement in formation of the photoanode in a dye sensitized solar cell is addressed. Specifically, a novel synthesis for the formation of a TiO2 precursor: titanium butanediolate, is detailed. This precursor is found to have higher thermal and temporal stability than commercially available TiO2 precursors and it has successfully been employed in the one-pot synthesis of rutile nanowires grown directly on a conducting substrate: fluorine doped tin oxide (FTO). This synthesis has been further extended to directly form a mixed phase TiO2 film consisting of rutile nanowires along with anatase spherical particles on FTO and this assembly has been used as the photoanode in a dye-sensitized solar cell. The synergistic effect of the two phases has provided a net DSSC efficiency of 4.61% with FF = 61%.
Keywords: Nanomaterials; Nanowires; TiO2

Facile gamma radiolytic methodology for TiO2-rGO synthesis: effect on photo-catalytic H-2 evolution - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dhara, S.; Dash, Sitaram; Tyagi, A. K. (International Journal of Hydrogen Energy, 2015)
TiO2 (P25) decorated reduced graphene oxide (rGO) is synthesized by gamma-radiolytic technique using water-ethanol solvent medium. Visible light absorpdon was confirmed by UV-Visible spectroscopy. Photoluminescence (PL) study revealed a decline in electron-hole recombination rate signalled by a sharp fall in luminescence of TiO2. Under such scenario, electron transfer from TiO2 conduction band to the conjugated sheet becomes a preferred pathway in the presence of rGO, which is further confirmed by photocurrent measurement. TiO2 -rGO composite with 1 wt. % rGO was found to be the best composition in terms of visible light absorption, while retaining TiO2 crystallinity. Transmission electron microscopy and Raman spectroscopic studies confirmed the coating of rGO sheet with TiO2 nanoparticles. TiO2 -rGO was found to show about 150 times higher photocatalytic H-2 generation under 250 W UV-Visible light irradiation than pristine TiO2. In addition to this, TiO2 -rGO composite shows hydrogen production yield of 35 mu mol/h.g under visible light (lambda = 400 nm) irradiation. Thus gamma-radiolysis can be considered to be a viable technique, which helps in synthesizing photocatalytically active nanocomposite with high H-2 evolution rate. In the light of these interesting aspects, a detail investigation is carried out to study the effect of rGO concentration and illumination time on photocatalytic yield. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: gamma-radiolysis; H-2 production; Photocatalysis; Reduced graphene oxide; TiO2

Selective aerobic oxidation of alcohols over Au-Pd/sodium titanate nanotubes - Nepak, Devadutta; Darbha, Srinivas (Catalysis Communications, 2015)
catalytic application of Au-Pd nanoparticles supported on sodium titanate nanotubes (NaTNTs) for liquid-phase aerobic oxidation of alcohols is reported, for the first time. This reaction occurs at 80-120 degrees C, 1 atm and solvent-/alkali-free conditions yielding the corresponding carbonyls in high selectivity. This catalyst was reusable and found to be more active/selective than the corresponding monometallic Au and Pd catalysts and Au-Pd/TiO2. Higher dispersion, smaller particle size and higher amount of electron density at gold are the causes for the superior activity of Au-Pd/NaTNT catalyst. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: aerobic oxidation; Alcohol; Bimetallic Au-Pd catalyst; Sodium titanate nanotubes; TiO2

Surface tailored PS/TiO2 composite nanofiber membrane for copper removal from water - Wanjale, Santosh; Birajdar, Mallinath S.; Jog, Jyoti Prakash; Neppalli, Ramesh; Causin, Valerio; Karger-Kocsis, Jozsef; Lee, Jonghwi; Panzade, Prasad (Journal of Colloid and Interface Science, 2016)
Polystyrene (PS)/TiO2 composite nanofiber membranes have been fabricated by electrospinning process for Cu2+ ions removal from water. The surface properties of the polystyrene nanofibers were modulated by introducing TiO2 nanoparticles. The contact angle of the PS nanofiber membrane was found to be decreased with increasing concentration of TiO2, depicted enhanced hydrophilicity. These membranes were highly effective in adsorbing Cu2+ ions from water. The adsorption capacity of these membranes was found to be 522 mg/g, which is significantly higher than the results reported by other researchers. This was attributed to enhanced hydrophilicity of the PS/TiO2 composite nanofiber membranes and effective adsorption property of TiO2 nanoparticles. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: electrospinning; Metal ion adsorption; Nanofiber; TiO2; Water treatment/purification

TiO2 modification by gold (Au) for photocatalytic hydrogen (H-2) production - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dash, Sitaram; Tyagi, A. K. (Renewable & Sustainable Energy Reviews, 2016)
TiO2 is indeed one of the widely used semiconductors employed for photocatalytic hydrogen production. Most of its photocatalytic activity-is achieved in its crystalline form. However, its photocatalytic activity is limited to ultraviolet region. For making TiO2 visible light active; Au deposition is strongly recommended due to its surface plasmon feature. Au deposition enhances the photocatalytic activity of both crystalline and nanocrystalline TiO2. Efficiency of photocatalytic activity is controlled by shape and size of Au nanoparticle subsequently the synthetic methodology plays an important role. Herein, we furnish a brief description of TiO2-Au nanocomposite synthesis by different methods viz. sol-gel, photodeposition, deposition-precipitation simple reducing method and dispersion method. A discussion on physical properties of the resultant material is also provided. Three different types of mechanism has been described depending on the type of irradiation and form of TiO2 (crystalline and nanocrytalline). A comparative hydrogen production yield is also tabulated to get an idea about the best synthesis methodology and form of TiO2 for efficient photocatalysis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gold nanoparticle; Hydrogen generation; Nanocomposite; Photocatalysis; TiO2

TiO2/RGO composites: Its achievement and factors involved in hydrogen production - Gupta, Bhavana; Melvin, Ambrose A. (Renewable &sustainable energy reviews, 2017)
The immense potential shown by TiO2 to participate as a designer material resulting into a new class of high performing photocatalyst has acclaimed it to become an important player in the designing and synthesis of various solar harvesting materials. This role has further been explored by the introduction of graphene into TiO2 matrix. TiO2/reduced graphene oxide (TiO2/RGO) or TiO2/graphene (TiO2/GR) has shown its prospects or relevance to be considered as the next generation photocatalyst for hydrogen production by its reported values in terms of producing hydrogen gas. Hence, there is a requirement of having a detailed up to date write up on the work done in this area in terms of its synthetic procedures, properties and its effect on hydrogen production. Herein, we discuss the different methods involved in the synthesis of such highly efficient materials followed by a brief explanation on its structural and morphological properties. Furthermore, a comparative study on the recent developments in terms of hydrogen evolution efficiency along with a mechanistic approach is also described. Finally, the current challenge and possibility of the future development in this direction is emphasized.
Keywords: Au-tio2 Photocatalysts; Evolution; Generation; graphene; Hydrogen generation; Nanocomposite; Nitrogen-doped Tio2; Photocatalysis; Photocatalytic H-2 Production; Recent Progress; Reduced graphene oxide; TiO2; Tio2-graphene Nanocomposites; Visible-light Irradiation; Water

Electronic integration and thin film aspects of Au-Pd/rGO/TiO2 for improved solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala P.; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2019)
In the present work, we have synthesized noble bimetallic nanoparticles (Au-Pd NPs) on a carbon-based support and integrated with titania to obtain Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2 nanocomposites using an ecofriendly hydrothermal method. Here, a 1:1 (w/w) Au-Pd bimetallic composition was dispersed on (a) high-surface-area (3000 m(2) g(-1)) activated carbon (Au-Pd/C), prepared from a locally available plant source (in Assam, India), and (b) reduced graphene oxide (rGO) (Au-Pd/rGO); subsequently, they were integrated with TiO2. The shift observed in Raman spectroscopy demonstrates the electronic integration of the bimetal with titania. The photocatalytic activity of the above materials for the hydrogen evolution reaction was studied under 1 sun conditions using methanol as a sacrificial agent in a powder form. The photocatalysts were also employed to prepare a thin film by the drop-casting method. Au-Pd/rGO/TiO2 exhibits 43 times higher hydrogen (H-2) yield in the thin film form (21.50 mmol h(-1) g(-1)) compared to the powder form (0.50 mmol h(-1) g(-1)). On the other hand, Au-Pd/C/TiO2 shows 13 times higher hydrogen (H-2) yield in the thin film form (6.42 mmol h(-1) g(-1)) compared to the powder form (0.48 mmol h(-1) g(-1)). While powder forms of both catalysts show comparable activity, the Au-Pd/rGO/TiO2 thin film shows 3.4 times higher activity than that of Au-Pd/C/TiO2. This can be ascribed to (a) an effective separation of photogenerated electron-hole pairs at the interface of Au-Pd/rGO/TiO2 and (b) the better field effect due to plasmon resonance of the bimetal in the thin film form. The catalytic influence of the carbon-based support is highly pronounced due to synergistic binding interaction of bimetallic nanoparticles. Further, a large amount of hydrogen evolution in the film form with both catalysts (Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2) reiterates that charge utilization should be better compared to that in powder catalysts.
Keywords: bimetal; Photocatalysis; surface plasmon resonance; TiO2; water splitting

Improved efficiency of DSSC using combustion synthesized TiO2 - Umale, Sanjivani; Sudhakar, V.; Sontakke, Sharad M.; Krishnamoorthy, K.; Pandit, Aniruddha B. (Materials Research Bulletin, 2019)
Combustion synthesis method is an economic, one step and an effective method for the synthesis of nanomaterials. In this work, titanium dioxide nanoparticles were synthesized by combustion method. The synthesized material was characterized by XRD, SEM and BET. Dye sensitized solar cell was fabricated using the synthesized material and its performance was compared with the solar cell fabricated using commercial TiO2. In order to evaluate the photovoltaic performance of DSSCs, photocurrent density to photovoltage (J-V) characteristic and electrochemical impedance spectroscopy (EIS) measurements were carried out. The DSSC fabricated using combustion synthesized and commercial TiO2 exhibited a power conversion efficiency of 6.11% and 6.62%, respectively. Combustion synthesized TiO2 which displayed similar efficiency to that of commercial material is least studied in the literature for solar cell applications.
Keywords: Combustion synthesis; Dye sensitized solar cell; TiO2

Aromatic amine passivated TiO2 for dye-sensitized solar cells (DSSC) with similar to 9.8% efficiency - Kumar, T. R. Naveen; Yuvaraj, S.; Kavitha, P.; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Neppolian, B. (Solar Energy, 2020)
In this work, the efficiency of dye-sensitized solar cells (DSSC) was improved by capping TiO2 with simple aromatic amines as a complexing agent. The aromatic amines, aniline and o-phenylenediamine capped TiO2 composites were synthesized via hydrothermal route and used as scattering layer in dye-sensitized solar cell (DSSC). Markedly, the maximum photo-conversion efficiency of 9.84% was achieved with o-phenylenediamine capped-TiO2 composite as o-phenylenediamine capped-TiO2 showed higher reflectivity than the pristine TiO2, which is highly beneficial for reflecting the photons back to photoanode. In addition, the average life time of carriers in o-phenylenediamine capped-TiO2 was found to be 9.8 ms, which was 2 times higher than the pristine TiO2 (4.29 ms).
Keywords: Aromatic amines; DSSC; Electron injection; lifetime; Scattering layer; TiO2

Rationally designed, efficient, and earth-abundant Ni-Fe cocatalysts for solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala Prabhakar; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2021)
Developing highly efficient and affordable catalysts for solar hydrogen (H-2) generation is crucial, and employing a cocatalyst from earth-abundant elements has a critical role to play. In this context, different compositions of earth-abundant Ni-Fe alloy (1:1, 1:3, and 3:1) have been prepared by hydrothermal method; subsequently, 1 wt % of these Ni-Fe cocatalysts were integrated with TiO2-P25 and thoroughly characterized. The resultant catalysts have been evaluated for solar H-2 production, in powder and thin film forms, under one sun condition and in direct sunlight. Interestingly, all the catalysts in the thin film form exhibit superior hydrogen yield (HY), up to 27 times higher activity than its powder counterpart. Among the photocatalysts, Ni-Fe/TiO2 (3:1 = Ni/Fe; NFT31) composition exhibits the best HY in thin film (8.27 mmol.h(-1).g(-1)) and exceeds all other compositions of catalyst. It is also to be reported that HY measured for the powder form with 1 mg shows 3-17 times higher activity than that measured with 25 mg. This is mainly attributed to effective solar light absorption with a smaller amount of photocatalyst either spread over large area in a thin film form or well-dispersed in suspension forms. Furthermore, the enhanced activity obtained with Ni-Fe/TiO2 photocatalysts is also ascribed to strong electronic integration of Ni-Fe cocatalyst with TiO2 and higher performance obtained with a thin film is attributed to increased charge carrier generation and subsequent charge separation and effective utilization. A decrease in work function of TiO2 by 0.6 eV was observed after its integration with cocatalyst in NFT31.
Keywords: Cocatalyst; Hydrogen; Ni-Fe alloy; solar energy; TiO2; water splitting

Scalable optical fiber reactor for photocatalytic H2 production: addressing scattering issues - Walko, Priyanka S.; Devi, R. Nandini (International Journal of Hydrogen Energy, 2023)
Scattering is one of the main challenges in scaling up photocatalytic water splitting using the most prevalent powder catalysts. This can be overcome by decoupling the reaction medium from light transmission, as in the case of optical fibers. Here we explore utilizing optical fibers coated with 5 wt% CuO supported on TiO2 for photocatlytic H2 production from water-methanol mixtures. CuO/TiO2 is a well studied photo catalyst in which photoreduced Cu species are known to act as sensitizers for inducing visible light activity. Lower activity of sequentially coated systems indicates that appropriate interfaces of active Cu and TiO2 with water are desirable. The scalability of such optical fiber-based systems along with potential in non-potable turbid water media are demonstrated. Maximum activity of 22 mmoles of H2 in 8 h was obtained with 50 mg of catalyst coated on optical fibers, which increases linearly with increase in fiber numbers, whereas, drastic reduction in activity is observed in powder catalyst upon increasing the catalyst quantity. A one-to-one comparison of 700 mg of catalyst in powder form and coated on optical fibers indicates more than one order enhancement in activity in the optical fiber based system. In addition, -70% retention in activity in highly turbid non-potable water was observed as compared to powdered system which shows complete reduction in the activity by 99.99%. (c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CuO; Optical fibers; photocatalytic water splitting; TiO2; Total internal reflection; Visible light utilisation